Religious Minorities in Pakistan: A Thematic Analysis of the Editorial Coverage of the Lynching of a Sri Lankan Citizen in Sialkot - Bukhari, Syed Abid Ali; Saleem, Nadia; Khan, Nauman (Annals of Human and Social Sciences, 2023)
The killing of a Sri Lankan activist Mr. Priyantha Kumara in Pakistan on charges of blasphemy became another burning issue in a series of similar incidents in Pakistan. A non-Muslim being killed for blasphemy in Pakistan is not unusual news. National and international media have reported various incidents in the recent past. This study is an attempt to find and analyze the main themes of the editorial content of the selected Pakistani and Sri Lankan newspapers regarding the lynching of Mr. Priyantha Kumara. We have employed thematic analysis as a theoretical and methodological framework to explore and comparatively analyze the editorial themes regarding the murder of Mr. Kumara. Our findings show that Pakistan’s leading newspaper The Express Tribune and Sri Lanka’s leading newspaper Daily Mirror both portrayed the incident as a heinous crime against humanity without fanning the flames of ’religious extremism’. Both the dailies described the perpetrators as irrational, barbaric and inhumane.